A charge-disproportionate ordered state with δ = 0.75 in a chemically sensitive donor/acceptor Dδ+2A2δ− layered framework1. Issue 37 (7th May 2015) - Fukunaga, Hiroki; Yoshino, Takafumi; Sagayama, Hajime; Yamaura, Jun-ichi; Arima, Taka-hisa; Kosaka, Wataru; Miyasaka, Hitoshi
<x xml:space="preserve">Abstract</x> A novel charge-disproportionation state with δ = 0.75 was observed in an electron-donor (D)/-acceptor (A) Dδ+2A2δ− layered framework by chemically tuning the electron-donating affinity of D.